2010
DOI: 10.1139/f10-021
|View full text |Cite
|
Sign up to set email alerts
|

Do in-stream restoration structures enhance salmonid abundance? A meta-analysis

Abstract: Despite the widespread use of stream restoration structures to improve fish habitat, few quantitative studies have evaluated their effectiveness. This study uses a meta-analysis approach to test the effectiveness of five types of in-stream restoration structures (weirs, deflectors, cover structures, boulder placement, and large woody debris) on both salmonid abundance and physical habitat characteristics. Compilation of data from 211 stream restoration projects showed a significant increase in pool area, avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
162
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(185 citation statements)
references
References 57 publications
16
162
1
1
Order By: Relevance
“…The most thorough meta-analysis of habitat and biological response to instream structure placement was conducted by Whiteway et al (2010). They examined salmonid response to wood and other structure placement using data from 211 streams from 51 different studies and found significant improvements in physical habitat and positive and significant responses for most species of salmonid fishes (Fig.…”
Section: Biological Response To Wood Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…The most thorough meta-analysis of habitat and biological response to instream structure placement was conducted by Whiteway et al (2010). They examined salmonid response to wood and other structure placement using data from 211 streams from 51 different studies and found significant improvements in physical habitat and positive and significant responses for most species of salmonid fishes (Fig.…”
Section: Biological Response To Wood Placementmentioning
confidence: 99%
“…3). In addition, Whiteway et al (2010) The strict data requirements of a formal meta-analysis often exclude the vast majority of studies done on wood placement (i.e., Stewart et al 2009;Whiteway et al 2010). Therefore, we conducted a simpler summary of results of papers that we located that examined fish response to wood placement to see how many reported positive, negative, or no fish response to wood placement.…”
Section: Biological Response To Wood Placementmentioning
confidence: 99%
“…For example, field experiments in the US Pacific Northwest have shown that trophic manipulations (e.g., nutrient additions or salmon carcass introductions) that boost the abundance of potential prey organisms also boost subsequent fish growth (7)(8)(9)(10). In contrast, restoration of physical habitats by creating pools or adding structures yields ambiguous evidence that such efforts increase subsequent fish abundance and biomass (11)(12)(13)(14)(15)(16)(17). Although it may be premature to conclude from these studies that food availability and species interactions are more limiting to fish than the quality or quantity of the physical habitat, evidence is mounting that many habitat restoration activities are not always as effective in meeting stated goals and objectives as originally anticipated.…”
mentioning
confidence: 99%
“…27 Research about the effectiveness of habitat modification finds mixed results, 28,29 though some methods, such as in-stream log and boulder structures, appear to be broadly successful. 30 California river restoration projects have become increasingly common in the last thirty years. 31 Close to $50M has already been invested in river and watershed restoration in the Russian River basin since 1980, primarily to counteract the effects of logging and other land development.…”
Section: The Prospectsmentioning
confidence: 99%